Identifying and prioritizing antifragile tourism strategies in a Neutrosophic environment - Mahdi Ghaforiyan; Ali Sorourkhah; Seyyed Edalatpanah (Journal of Fuzzy Extension and Applications)
Tourism is a worthy catalyst for development in emerging economies and supports growth in most developing countries. Consequently, countries continuously strive to enhance tourism competitiveness to magnetize worldwide tourists. However, due to significant environmental changes and intense competition, tourism organizations are compelled to adopt new strategies. A literature review demonstrates a broad spectrum of possible and available strategies for countries to choose from, necessitating the prioritization of strategies appropriate to the host country's situation and conditions. In this study, we implemented the Antifragility Analysis Algorithm (AAA) to address the research problem (identifying and prioritizing tourism strategies in the western region of Mazandaran province, Iran). We also collected experts' verbal judgments using Neutrosophic Sets (NSs), which can effectively address ambiguity and uncertainty. Initially, with the help of experts in the field, we identified eleven available strategies. Then, we identified five influential environmental indicators and possible states for each, defining thirteen alternative scenarios (one current scenario and twelve future scenarios). Subsequently, the performance of strategies in each indicator state was estimated using NSs. Then, considering the future scenarios, the antifragility scores of the strategies were determined. The results indicate all listed strategies are antifragile, meaning that adopting and implementing each could yield more significant benefits than the current situation. According to the findings, market research, infrastructure development, community engagement, diversification, and monitoring strategies should be implemented in the initial stage. Following them, destination branding, halal tourism, and crisis management strategies should be implemented in the next stage, and the remaining strategies can be executed in the final stage.